A Diamine‐Oriented Biorefinery Concept Using Ammonia and Raney Ni as a Multifaceted Catalyst. Issue 11 (19th September 2022) - Wu, Xianyuan; De bruyn, Mario; Barta, Katalin
Abstract: Diamines are important industrial chemicals. In this paper we outline the feasibility of lignocellulose as a source of diol‐containing molecules. We also illustrate the possibility of turning these diols into their diamines in good to excellent yields. Central to these transformations is the use of commercially available Raney Ni. For diol formation, the Raney Ni engages in hydrogenation and often also demethoxylation, that way funneling multiple components to one single molecule. For diamine formation, Raney Ni catalyzes hydrogen‐borrowing mediated diamination in the presence of NH3 . Abstract : This work describes a novel sustainable biorefinery strategy, through which a range of biomass‐derived diols and high value diamines can be produced in excellent yields. Central to this is the use of Raney Ni, which engages in demethoxylation, hydrogenation, and amination, the latter following a hydrogen borrowing strategy.